An introduction to patient-reported outcome measures (PROMs) in trauma. Issue 2 (February 2019) - Turner, Grace M.; Slade, Anita; Retzer, Ameeta; McMullan, Christel; Kyte, Derek; Belli, Antonio; Calvert, Melanie
Abstract : ABSTRACT: Increased survival rates from traumatic injury have resulted in more people living with disability and reduced quality of life. To understand how peoples' quality of life is affected following a traumatic injury and the effects of that injury on their health and well-being, it is important to capture patients' perspectives of their own health. Patient-reported outcome measures (PROMs) are questionnaires, completed by patients, which can be used to measure the symptom burden associated with trauma and its treatment, and impact on quality of life. Patient-reported outcome measures have a wide variety of uses that are relevant to trauma. In a research setting, PROMs can be used to assess the effectiveness of treatment and burden of disease. In a clinical setting, PROMs have the potential to inform and guide patient-centered care and clinical decision making. Collected as part of trauma registries, PROMs can be used at an aggregate level to inform improvements and uphold the quality of trauma care. This literature review explores and summarizes the key current and potential future uses of PROMs in trauma research, routine clinical practice, and registries.